Evelyn's Husband - Chesnutt, Charles W. (Charles Waddell), 1858-1932 (Book collections on Project MUSE., 2005)
The critique of white male society that Charles W. Chesnutt launched in A Marrow of Tradition continues in Evelyn's Husband, one of six manuscripts left unpublished when this highly regarded African American innovator died. Set in Boston society, on a deserted Caribbean island, and in Brazil, Evelyn's Husband is the story of two men-one old, one young-in love with the same young woman. Late in his career Chesnutt embarked on a period of experimentation with eccentric forms, finishing this hybrid of a romance and adventure story just before publishing his last work, The Colonel's Dream. In.